Development of a novel method for the enrichment of unsubstituted naphthalene and phenanthrene from crude oils for compound-specific stable isotope analysis. Issue 35 (21st August 2017) - Chen, Yongxin; Zhang, Xilong; Chang, Jiang; Ma, Suping; Wu, Yingqin; Xia, Yanqing
Abstract : A novel, effective and easy-to-operate method to enrich unsubstituted naphthalene and phenanthrene directly from crude oils was developed based on closed-system pyrolysis. Abstract : A novel, effective and easy-to-operate method to enrich unsubstituted naphthalene and phenanthrene directly from crude oils was developed based on closed-system pyrolysis. The pyrolysis at 500 °C for 12 h was found to be sufficient for the enrichment of unsubstituted aromatics that were free of unresolved complex mixture (UCM) and poly-substituted aromatics. This allowed further accurate compound specific isotope analysis, and GC-IRMS data showed that the δ 13 C values of unsubstituted naphthalene and phenanthrene had no obvious fractionation during the enrichment process. This method provides an easy-to-operate pre-concentration technique for unsubstituted aromatics suitable for compound-specific isotope analysis (CSIA), laying the foundation for developing new oil–oil correlation indicators.